2016
DOI: 10.1155/2016/3439707
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy, Safety, and Cost Benefit of Olanzapine versus Aprepitant in Highly Emetogenic Chemotherapy: A Pilot Study from South India

Abstract: Background. The efficacy, safety, and cost benefit of olanzapine (OLN) when compared to aprepitant (APR) in the prevention of chemotherapy induced nausea and vomiting (CINV) in patients receiving highly emetogenic chemotherapy (HEC) were evaluated. Methods. A prospective pilot study was done in chemotherapy-naive patients receiving HEC to compare OLN versus APR along with palonosetron and dexamethasone. 100 patients consented to the protocol and were randomized and evaluated for Complete Response (CR) (no emes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 20 publications
0
54
1
Order By: Relevance
“…A Phase II study [16] also showed that olanzapine combined with a single dose of dexamethasone, and a single dose of palonosetron was very effective in controlling acute and delayed CINV in patients receiving both HEC and MEC. A recent study [30] evaluated the efficacy, safety, and cost benefit of olanzapine as compared to aprepitant for the prevention of CINV in patients receiving palonosetron and dexamethasone combination regimens. There was no difference in safety and efficacy but olanzapine was a cost-effective alternative to aprepitant.…”
Section: Discussionmentioning
confidence: 99%
“…A Phase II study [16] also showed that olanzapine combined with a single dose of dexamethasone, and a single dose of palonosetron was very effective in controlling acute and delayed CINV in patients receiving both HEC and MEC. A recent study [30] evaluated the efficacy, safety, and cost benefit of olanzapine as compared to aprepitant for the prevention of CINV in patients receiving palonosetron and dexamethasone combination regimens. There was no difference in safety and efficacy but olanzapine was a cost-effective alternative to aprepitant.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the studies were double-blinded RCTs20,32, three were single blinded and the rest were unblinded. Finally, 8 studies reported participants of Asian background; two from India30,31, one from Japan29 and five from China 24-28. Five of the studies reported that the patients included where from USA 20-23,32…”
Section: Resultsmentioning
confidence: 99%
“…Many randomized controlled trials (RCTs) have been then conducted to confirm the effect of addition of olanzapine to the standard antiemetic regimen 20,21,22,23,24,25,26,27,28,29,30,31,32. A previous meta-analysis conducted by Wang et al33 revealed that the rate of patients achieving total control of nausea and vomiting was significantly higher in the olanzapine group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, although 5CN is recommended by ESMO guidelines, there is no direct evidence concerning the relative efficacy between 5CO and 5CN in the setting of AC‐based chemotherapy. Only two publications characterized by unspecific chemotherapy have reported that both combinations have no significant disparity in terms of acute CINV prophylaxis . Moreover, there is no mechanistic advantage of 5CN since the peripheral pathway is the primary signaling responsible for acute CINV, which involves serotonin receptors instead of neurokinin transduction .…”
Section: Discussionmentioning
confidence: 99%